KRITIK SOSIAL MASALAH KELUARGA DAN KEBUDAYAAN DALAM NOVEL BEDEBAH DI UJUNG TANDUK KARYA TERE LIYE - Jamlean, Agustin Clarita; Pramujiono, Agung; Indayani, Indayani (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the social criticism of family problems and cultural problems in the novel Bedebah di Ujung Tanduk by Tere Liye. Novels can be an education that can be used as a form of social criticism, judgment, and role model. This research method uses the hermeneutic method with a qualitative descriptive approach. The data source of this research is the novel Bedebah di Ujung Tanduk by Tere Liye, and the data used is a choice of words, phrases, and sentences that state aspects of social criticism of family problems and social criticism of cultural problems. The data collection technique used by researchers to obtain data is the documentation technique. This documentation technique uses documents in the form of books, in this case novels, by doing two stages, namely reading and recording. The data analysis technique uses interactive methods, according to Miles and Huberman, which consist of data analysis, data reduction, and data presentation. The results show that the social criticism of family problems in this study includes domestic violence, parents who do not carry out their roles properly, and disharmonious families. The social criticism of cultural issues found in this study includes individual behavior, honesty, cooperation, and inheritability.